TVET policy reforms in Chile 2006-2018 : between human capital and the right to education - Zancajo, Adrian [Verfasser]; Valiente, Oscar [Verfasser] (My University, 2019)
"Human development and rights-based approaches to education have been gaining support among international organisations and development agencies as alternative frameworks to human capital orthodoxy. While these global trends have been well-documented in the international development literature, there is little empirical evidence into what extent, and through which mechanisms, alternative development paradigms in education are influencing Technical and Vocational Education and Training (TVET) reforms. Chile provides an excellent opportunity for this kind of research given the long cycle of political contestation of neoliberal education policies in the country during the last decade. The article analyses TVET policy discourses for the last three government administrations (2006–2018) from a Cultural Political Economy perspective. The adoption of the rights-based approach in Chile shows its potential to mobilise greater involvement of the state in the funding and provision of TVET and in the support to secondary TVET students who want to continue their studies in tertiary education. However, the rights-based approach to education falls short when it comes to problematising political economy structures that shape TVET policymaking and the precarious labour market opportunities available to TVET graduates. These shortfalls show the need to incorporate more fundamental critiques of the neoliberal paradigm into the formulation of alternative policy agendas for TVET." (authors' abstract ; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.3.3 Lateinamerika; Berufsbildungspolitik; Recht auf Ausbildung; Bildungschancengleichheit; Chile